2021
DOI: 10.1038/s41467-021-23207-8
|View full text |Cite
|
Sign up to set email alerts
|

Sensing of joint and spinal bending or stretching via a retractable and wearable badge reel

Abstract: Human motions, such as joint/spinal bending or stretching, often contain information that is useful for orthopedic/neural disease diagnosis, rehabilitation, and prevention. Here, we show a badge-reel-like stretch sensing device with a grating-structured triboelectric nanogenerator exhibiting a stretching sensitivity of 8 V mm−1, a minimum resolution of 0.6 mm, a low hysteresis, and a high durability (over 120 thousand cycles). Experimental and theoretical investigations are performed to define the key features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(76 citation statements)
references
References 40 publications
0
76
0
Order By: Relevance
“…Apart from the movements of upper limbs, spinal bending is also essential towards a more complete pose monitoring. A badge-reel-like stretch sensor based on a similar grating-structured TENG was reported by Li et al as shown in Figure 3h [173]. By analyzing the generated peaks' number, high sensitivity of 8 V mm −1 and a minimum resolution of 0.6 mm with good robustness and low hysteresis can be achieved for this wearable badge reel, which can be used for patients' spinal shape change monitoring when serving as a rehabilitation brace.…”
Section: Other Wearable Hmismentioning
confidence: 76%
“…Apart from the movements of upper limbs, spinal bending is also essential towards a more complete pose monitoring. A badge-reel-like stretch sensor based on a similar grating-structured TENG was reported by Li et al as shown in Figure 3h [173]. By analyzing the generated peaks' number, high sensitivity of 8 V mm −1 and a minimum resolution of 0.6 mm with good robustness and low hysteresis can be achieved for this wearable badge reel, which can be used for patients' spinal shape change monitoring when serving as a rehabilitation brace.…”
Section: Other Wearable Hmismentioning
confidence: 76%
“…Eventually, virtual training demonstrations of ping-pong program and punch program are realized real-time processing by equipping this exoskeleton. In Figure 6d, Li et al reported a retractable and wearable badge reel-based sensor with a grating structured TENG for sensing the joint's and spinal's bending or stretching [240]. Compared above mechanical structures that rely on limbs' motions, this sensor has a light weight of 9.6 g, a diameter of 33 mm, and a thickness of 10 mm.…”
Section: Human Monitoringmentioning
confidence: 99%
“…As a new energy harvesting technology, triboelectric nanogenerator (TENG) has invoked intense research interests since its invention in 2012. Based on the coupling effect of triboelectrification and electrostatic induction [16] , [17] , [18] , [19] , TENG can effectively harvest all kinds of mechanical energy in the environment [20] , including human motion [21] , [22] , [23] , wind energy [24] , [25] , [26] , water energy [27] , [28] , tire rotating energy [29] , vibration energy and so on. TENG is widely used in wearable [30] , intelligent sensing [31] , [32] , [33] , [34] , biomedical [35] , environmental protection [36] and other fields.…”
Section: Introductionmentioning
confidence: 99%